Efektivitas Poster Kampanye Grace Natalie Dalam Meningkatkan Awareness Mahasiswa - Angelita Kania Ramdan; Vera Wijayanti Sutjipto (DIII Prodi Humas Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2020)
In the 2019 general election, PSI or the Indonesian Solidarity Party which was formed in 2014 carried one of the candidates who is the chairman of PSI itself, Grace Natalie. As a new party, PSI certainly has certain strategies to increase public awareness of PSI, especially towards Grace Natalie as one of the candidates promoted by PSI. This study aims to determine the effectiveness of the poster used as a Grace Natalie campaign tool in increasing student awareness about Grace Natalie as one of the candidates promoted by PSI. The population of this study were students of the Communication Science class of 2018 Universitas Negeri Jakarta.. The results of this study showed that the poster was an effective media in increasing awareness among students of the Communication Studies Program class of 2018 Universitas Negeri Jakarta.